Isolation and characterization of 9-lipoxygenase and epoxide hydrolase 2 genes: insight into lactone biosynthesis in mango fruit (Mangifera indica L.) - Deshpande, Ashish B.; Chidley, Hemangi G.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2017)
Uniqueness and diversity of mango flavour across various cultivars are well known. Among various flavour metabolites lactones form an important class of aroma volatiles in certain mango varieties due to their ripening specific appearance and lower odour detection threshold. In spite of their biological and biochemical importance, lactone biosynthetic pathway in plants remains elusive. Present study encompasses quantitative real-time analysis of 9-lipoxygenase (Mi9LOX), epoxide hydrolase 2 (MiEH2), peroxygenase, hydroperoxide lyase and acyl-CoA-oxidase genes during various developmental and ripening stages in fruit of Alphonso, Paid and Kent cultivars with high, low and no lactone content and explains their variable lactone content. Study also covers isolation, recombinant protein characterization and transient over-expression of Mi9LOX and MiEH2 genes in mango fruits. Recombinant Mi9LOX utilized linoleic and linolenic acids, while MiEH2 utilized aromatic and fatty acid epoxides as their respective substrates depicting their role in fatty acid metabolism. Significant increase in concentration of delta-valerolactone and gamma-decalactone upon Mi9LOX over-expression and that of delta-valerolactone, gamma-hexalactone and delta-hexalactone upon MiEH2 over-expression further suggested probable involvement of these genes in lactone biosynthesis in mango. (C) 2017 Elsevier Ltd. All rights reserved.

Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste